A dual dynamic chamber system based on IBBCEAS for measuring fluxes of nitrous acid in agricultural fields in the North China Plain. (January 2019) - Tang, Ke; Qin, Min; Duan, Jun; Fang, Wu; Meng, Fanhao; Liang, Shuaixi; Xie, Pinhua; Liu, Jianguo; Liu, Wenqing; Xue, Chaoyang; Mu, Yujing
Abstract: A dual dynamic chamber system combined with incoherent broadband cavity enhanced absorption spectroscopy (IBBCEAS) was first developed to measure nitrous acid (HONO) emission fluxes from agricultural fields in the North China Plain. The concentrations of HONO were measured with two IBBCEAS instruments in the sample and blank chambers, respectively. To ensure the accuracy and reliability of flux measurement, before the dynamic chamber system was deployed in an agricultural field, the correlation and accuracy of the two IBBCEAS instruments were tested, and the mixing uniformity of the gas in the chamber was verified. Within a week after fertilization, the observed HONO flux exhibited a pronounced diurnal variation profile with a maximum of 20.25 ng N m −2 s −1 at noontime and a minimum of −0.86 ng N m −2 s −1 in the early morning, one order of magnitude higher than the flux observed in previously reported literature from fields. During this period, the concentrations of HONO in both of the chambers was higher in the daytime than that nighttime, and the concentration of HONO in blank chamber reached the maximum of 18.88 ppbv at noon on the 5th day after fertilization. HONO and NO2 in the sample chambers showed opposite diurnal profiles. The field observation results suggested that the high HONO flux is mainly from the direct emission of soil rather than from the heterogeneous reaction of NO2 . Agricultural fertilization will affect the balance of the HONO budget, and then affect the atmospheric oxidation in the North China Plain. Highlights: A dynamic chamber system was first applied to measure HONO flux from farmland. Peak HONO emission was found after fertilization in farmland. The observed HONO flux exhibited a pronounced diurnal variation profile. The N-fertilized soils have a strong potential for HONO emissions.